Roasts - Good Housekeeping Institute (Great Britain)
Although eating habits have changed dramatically over the years, a traditional roast with various trimmings forms the centrepiece of a perfect weekend. This guide presents recipes from ginger and honey-glazed ham to goose with roasted apples - and the techniques section covering fish, poultry, meat, vegetables and sauces.